Experimental Measurements on a Stand for a Grain Sampler - Cezova, Eliska; Lopot, Frantisek; Machac, Martin; Kamenicky, Josef (Manufacturing Technology Journal, 2022)
This paper describes experimental measurements of travel rollers on a polyurethane thread. This exper-iment took place at the CTU Faculty of Mechanical Engineering in the laboratory of the Department of Design and Machine Parts. The experiment was performed within the project of a lightweight type of sampler, designed by a team of collaborators from our institute for OK Servis BioPro, s.r.o. For the new-ly designed type of sampler, it was necessary to determine the operation of a newly designed grain sampler. The load of the rollers is different in each environment. This paper presents the average values from the measurement, including its evaluation. Moreover, the paper compares different temperatures that can be achieved in the practice. Negative temperature values were not performed, as this meas-urement would be expensive and inefficient.
Keywords: Grain sampler; Experiment; Measurement; Travel roll; Polyurethane